Marine mammals : evolutionary biology - Berta, Annalisa; Sumich, James L.; Kovacs, Kit M., 1956- (Elsevier, Academic Press, 2015)
Marine Mammals: Evolutionary Biology, Third Edition is a succinct, yet comprehensive text devoted to the systematics, evolution, morphology, ecology, physiology, and behavior of marine mammals. Earlier editions of this valuable work are considered required reading for all marine biologists concerned with marine mammals, and this text continues that tradition of excellence with updated citations and an expansion of nearly every chapter that includes full color photographs and distribution maps.